2020
DOI: 10.1111/ggi.13929
|View full text |Cite
|
Sign up to set email alerts
|

Dual sensory impairment and healthcare use: Findings from a nationally representative sample

Abstract: Aim Dual sensory impairment (DSI) is a common phenomenon in later life. However, only a few studies investigated whether DSI is associated with healthcare use. Therefore, our purpose was to determine whether DSI is associated with healthcare use among older adults. Methods Data were taken from the most recent sixth wave of the German Ageing Survey. When self‐reported hearing problems and visual impairment were both present, individuals were classified as dual sensory impaired. The frequency of general practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
5
2
Order By: Relevance
“…One study reported a 58.6% prevalence of DSI among adults aged 45 years or older25; another study documented the prevalence of self-reported HI only, VI only and DSI in older Chinese adults being 5.7%, 22.2% and 58.6%, respectively;27 there was also literature focusing on long-lived individuals over 95 years of age in China and reported even higher prevalence among them: 66.1% of VI and 87.3% of HI 23. However, our estimates of SI prevalence seemed much higher than those reported in other studies from China (11.8% HI only, 6.3% VI only and 2.1% DSI28) and countries such as Korea (12.4% DSI29), Europe (eg, 34.4% either HI or VI, and 15.8% DSI in Germany30; 13.5% HI only, 10.2% VI only and 5.9% DSI in 11 European countries31), Canada (1.9% DSI32) and USA (24.4% HI only, 14.5% VI only and 18.2% DSI33). The discrepancies in prevalence rates across studies might be attributed to varieties in SI measurements (eg, self-reports or objective assessments) and participant characteristics (eg, age, race).…”
Section: Discussioncontrasting
confidence: 84%
“…One study reported a 58.6% prevalence of DSI among adults aged 45 years or older25; another study documented the prevalence of self-reported HI only, VI only and DSI in older Chinese adults being 5.7%, 22.2% and 58.6%, respectively;27 there was also literature focusing on long-lived individuals over 95 years of age in China and reported even higher prevalence among them: 66.1% of VI and 87.3% of HI 23. However, our estimates of SI prevalence seemed much higher than those reported in other studies from China (11.8% HI only, 6.3% VI only and 2.1% DSI28) and countries such as Korea (12.4% DSI29), Europe (eg, 34.4% either HI or VI, and 15.8% DSI in Germany30; 13.5% HI only, 10.2% VI only and 5.9% DSI in 11 European countries31), Canada (1.9% DSI32) and USA (24.4% HI only, 14.5% VI only and 18.2% DSI33). The discrepancies in prevalence rates across studies might be attributed to varieties in SI measurements (eg, self-reports or objective assessments) and participant characteristics (eg, age, race).…”
Section: Discussioncontrasting
confidence: 84%
“…Our study reported a 58.6% prevalence of DSI among older adults, which was higher than that in other countries, such as Korea (12.4%) (Kim et al, 2015), United States (18.2%) (Deardorff et al, 2019), and Germany (15.8%) (Hajek & Konig, 2020). One possible reason might be the difference in the measures of DSI across different studies.…”
Section: Discussioncontrasting
confidence: 68%
“…In recent years, there has been increasing interest in people with concurrent losses of both senses, or dual sensory impairment (DSI). 7,8 DSI, sometimes referred to as deaf blindness is a condition where hearing and visual impairment occur concurrently. Older adults with DSI were reported with the greatest decline in different physical and cognitive abilities and rates of mortality as compared with those with single sensory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers typically studied hearing loss and visual loss in isolation and in different groups of subjects, 5,6 making it impossible to determine how these two sensory losses interact with each other. In recent years, there has been increasing interest in people with concurrent losses of both senses, or dual sensory impairment (DSI) 7,8 . DSI, sometimes referred to as deaf blindness is a condition where hearing and visual impairment occur concurrently.…”
Section: Introductionmentioning
confidence: 99%